Stereocomplexation of PLL/PDL–PEG–PDL blends: Effects of blend morphology on film toughness. (August 2015) - Tacha, Sunan; Saelee, Tinnakorn; Khotasen, Wootichai; Punyodom, Winita; Molloy, Robert; Worajittiphon, Patnarin; Meepowpan, Puttinan; Manokruang, Kiattikhun
Graphical abstract: Highlights: Polylactide was toughened by stereocomplexation adopting PDL–PEG–PDL copolymers. AFM images showed the Sc-crystallites dispersed in a continuous amorphous phase. Increasing PDL segment length leaded to the increase of Sc-crystallite size. The increase of Sc-crystallite size resulted in the increase of tensile strength. Toughness depended on the balance between Sc-crystallite size and % amorphous area. Abstract: Polylactide (PL) finds its use in a wide variety of applications ranging from medical devices to engineering plastics. However, the use of PL is limited to certain applications due to its brittle characteristic and low heat distortion temperature, which indicate its poor mechanical and thermal properties, respectively. This present work demonstrated the toughening of PL by stereocomplexation adopting poly(d -lactide)–poly(ethylene glycol)–poly(d -lactide) (PDL–PEG–PDL) copolymers with various PDL segment length. The DSC results showed that the complete stereocomplexation was reached when 40 wt% copolymer was blended with poly(l -lactide) (PLL). In addition, the crystallization of PEG was interrupted and, thus, prohibited by either adding PDL or PLL in the system. AFM images showed that, for the first time, the stereocomplex crystallites (Sc-crystallites) formed by the enantiomer pairs were dispersed in a continuous amorphous phase of PL and the non-crystallizing PEG. The increase of PDL segment length in the copolymer leaded to the increase of the Sc-crystallite size, which, consequently, resulted in the increase of the tensile strength of the blended-films. Elongation at break of the films was found to rely on the determined amorphous area. To maximize the toughness of the films, the specific ratio of PDL and PEG segment length in the copolymer must be achieved to provide the optimum balance between Sc-crystallite size and % amorphous area.